Data Integration and Lecturer Expertise: Its Relevance to the Academic Reputation of the Faculty of Languages and Arts UNNES - Zustiyantoro, Dhoni; Mulyono, Mulyono; Sriyadi, Sriyadi (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
Academic reputation in higher education is important and needs to be improved, especially to answer the challenges of the academic world and the increasingly diverse scientific contributions. One way that can be done to improve academic reputation is by presenting complete and valid lecturer data. With complete and professional data on lecturers' expertise, it is hoped that the academic community at the national and international levels can quickly obtain information about lecturers who are expected to work together in the tri dharma and institutional fields. This research is an initial study to show the importance of data integration and lecturers' expertise. The Faculty of Languages and Arts supports the vision of Universitas Negeri Semarang (UNNES) to become “a university with a conservation perspective and with an international reputation.” To achieve this, strengthening academic reputation at the global level is an absolute must.